Student Perceptions of a Revise and Resubmit Policy for Writing Assignments. Issue 3 (September 2018) - Garner, Benjamin; Shank, Nathan
Effective writing is a soft skill that is highly in demand in today's workforce. This qualitative study examines student perceptions of a revise and resubmit policy aimed at increasing student engagement with an instructor's writing feedback and ultimately improving students' writing skills. Students across three business communication courses were offered bonus points if they made revisions and documented those revisions. The findings suggest that students were willing to complete a revision even if given only a small grade incentive. While some expressed negativity toward the extensive feedback, others viewed the revision option as a rare but valuable opportunity.